The The Effect of Micro Geometry with Various Forms as Passive Flow Control in NACA 4415: Pengaruh Geometri Berukuran Mikro Dengan Variasi Bentuk Sebagai Kontrol Aliran Pasif di NACA 4415 - James Julian; Rizki Aldi Anggara; Fitri Wahyuni; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2023)
This study investigates the effect of variations in the micro geometry with various forms as passive flow control devices on the aerodynamic capability of the airfoil. Micro-cylinder, micro-slat, and micro-cube are installed close to the leading edge of the NACA 4415 airfoil as a micro geometric variation of passive flow control devices with a predetermined diameter of 3% c located at coordinates x= 0% c and y= 8 %c of the leading edge of the airfoil. The Reynolds number used in this study is Re = with AoA variations from 0°-30°. This study's results show a decrease in Cl of 12% with a micro-cylinder, 26% with a micro-slat, and 28% with a micro-cube. In addition, the Cd produced by using the variation of the device micro geometry has increased significantly. Thus, the final result is a lift-to-drag ratio of more petite than the without micro. In the streamlined contour shown when the airfoil is at a high angle of attack, the use of micro geometric variations of passive flow control devices can have an effect that causes reduced recirculation that occurs in the airfoil. However, the impact of these devices is not optimal, resulting in a reduction in the aerodynamic capability of the NACA 4415 airfoil.